Evaluating the effectiveness of the process of hydration and hardening of hydraulic binders magnesia with simultaneous thermal analysis; International Conference on Thermal Analysis and Calorimetry in Russia (RTAC-2016); Vol. 1 - Mitina N. A. Nataliya Aleksandrovna (Section 1: Thermal analysis and calorimetry of inorganic substances and materials, 2016)
The article presents the results of the study of structure waterproof hydraulic magnesia binder in the process of hydration and hardening. Studies conducted using the combined thermal analysis (TG / DTA). It is shown that the process of curing in humid conditions hydrocarbonate of magnesia binder is most effective due to the increase of hydrocarbon products, which was an increase of peaks at 405.4 ° C in curves TG/DTA.